A postmortem study on the weight of the human adrenal glands (Bangladesh Journal of Medical Science, 2010)
Objective: A cross-sectional descriptive type of study was designed to find out the difference in weight of the right and left adrenal glands of Bangladeshi people in relation to age and to compare with the previous studies. Materials & Methods: The study was done in the Department of Anatomy, Dhaka Medical College, Dhaka from July 2008 to June 2009 and performed on 140 post mortem human adrenal glands collected from 70 unclaimed dead bodies which were in the morgue under examination in the Department of Forensic Medicine, Dhaka Medical College, Dhaka. The samples were divided into four age-groups including group A (11-20 years), group B (21-30 years), group C (31-40 years) & group D (41-60 years) and the weight of the adrenal glands were measured and recorded. Results: There was no difference found in weight in between the right and the left adrenal glands in any age group. For the right adrenal gland, the differences in weight between group A & group B and group A & group D were statistically significant (p